PROJECT MANAGEMENT METHODS FOR REENGINEERING THE ORGANIZATION'S BUSINESS PROCESSES - PILIAVOZ, Tetiana; SHVARTS, Iryna; KRAEVSKYI, Andriy; PUSTILNIK, Ilona (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes modern methods of project management for reengineering an organization's business processes. It is established that project management allows solving a large number of tasks in the process of creating new, modernizing and developing existing systems and technological processes at various enterprises and organizations as efficiently and efficiently as possible. Project management and business processes of an enterprise are aimed at obtaining a useful result.Reengineering is the restructuring of an organization's business processes to achieve a significant effect in reducing costs, improving quality, and increasing sales of products and services. The reengineering of an organization's business processes is a project activity, and therefore, project management standards and methods can be applied to it. A business process reengineering project is a purposeful activity that results in changes to an organization's set of business processes that are necessary to achieve its business goals.The choice of project management methods requires consideration of many factors, including project specifics, customer requirements, risks, and resources. An integrated approach to this issue helps ensure high quality project management and market competitiveness.Studies of existing project management methods have shown that the most relevant are agile project management methods: Scrum, Kanban, and Lean. They are focused on maximum adaptability to change, cooperation with the client, and the highest level of responsiveness to new requirements.The prospects for the development of flexible management methods include the possibility of using variations of the proposed approaches at different stages of the implementation of projects to reengineer the organization's business processes.
Keywords: reengineering; business processes; project; project management; Scrum; Kanban; Lean